“NAHJUL FARODIS” IS A RARE SAMPLE OF THE OLD UZBEK LITERARY LANGUAGE - Abduvalieva Dilnoza Akramovna (Zeta Repository, 2023)
Turning to written monuments is one of the important steps in solving problems related to language, history, and culture of a certain period. Therefore, it is necessary to convey the spiritual and material heritage of our ancestors to today's generation as it really is, to research them on a scientific basis. The only scientific way to study any language phenomenon historically is to identify similarities, differences and innovations between the two based on primary sources and comparing the language of written monuments. One of such rare works is Mahmud ibn Ali al-Sarayi's "Nahjul Farodis" ("The Open Way of Paradise") (1357-1358), one of the samples of Turkish prose of the 14th century. This article provides detailed information about the work “Nahjul Faradis”, a rare example of the old Uzbek literary language, its creation, the manuscript copies of the work that have reached us and the research conducted on the manuscript copies.